2010
DOI: 10.1042/cs20100094
|View full text |Cite
|
Sign up to set email alerts
|

The vascular contribution to Alzheimer's disease

Abstract: AD (Alzheimer’s disease) is a progressive neurodegenerative disease of unknown origin. Despite questions as to the underlying cause(s) of this disease, shared risk factors for both AD and atherosclerotic cardiovascular disease indicate that vascular mechanisms may critically contribute to the development and progression of both AD and atherosclerosis. An increased risk of developing AD is linked to the presence of the apoE4 (apolipoprotein E4) allele, which is also strongly associated with increased risk of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
0
6

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(83 citation statements)
references
References 218 publications
1
76
0
6
Order By: Relevance
“…Furthermore, perturbations in vascular hemodynamics have been observed in VaD and AD [136,137], however, AD patients had comparatively less impairment in cerebral perfusion than those with VaD [138] suggesting that hemodynamic disturbances may underlie different types of dementia [138]. While the precise mechanism that vascular risk factors initiate cognitive decline remains elusive [139], T2DM have been identified as an important contributing factor to the development of VaD.…”
Section: Vascular Dementia Versus Alzheimer's Dementiamentioning
confidence: 99%
“…Furthermore, perturbations in vascular hemodynamics have been observed in VaD and AD [136,137], however, AD patients had comparatively less impairment in cerebral perfusion than those with VaD [138] suggesting that hemodynamic disturbances may underlie different types of dementia [138]. While the precise mechanism that vascular risk factors initiate cognitive decline remains elusive [139], T2DM have been identified as an important contributing factor to the development of VaD.…”
Section: Vascular Dementia Versus Alzheimer's Dementiamentioning
confidence: 99%
“…It can promote amyloid deposition, neurotoxicity, oxidative stress, neurofibrillary tangle formation, and increasing brain inflammation. Previous studies have shown that ApoE4 causes mitochondrial damage, microvascular generation, and neural injury (24).…”
Section: Other Pathogenesesmentioning
confidence: 99%
“…Despite the fact that etiology and pathogenesis of AD have not been fully studied so far [5], the diagnosis of pre-clinical and early forms of the disease was named one of the major foci in AD studies at AAIC 2011. Such diagnosis will make possible an early treatment which is naturally more effective [6].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there have been a lot of large-scale studies on the vascular factor in the development of AD [5,[22][23][24][25][26][27], cerebral blood flow disorders [28,29], and the phenomena of amyloid angiopathy [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%